Treatment Of Prolapsus Bulbus Oculi In Domestic Cats - Sukma, Zahwa Tamara; Darmawi, Darmawi; Sayuti, Arman; Amiruddin, Amiruddin; Syafruddin, Syafruddin; Daud, Razali; Erwin, Erwin; Panjaitan, Budianto; Ferdian, Riyan; Zamzami, Rumi Sahara; Usrina, Nora; Akmal, Muslim; Balqis, Ummu (Jurnal Medika Veterinaria, 2025)
Bulbus oculi prolapse is a condition characterized by the protrusion of the eyeball from the eye socket, which can be caused by various factors such as trauma, elevated intraocular pressure, and abnormalities in the eye muscles. This case study aimed to examine the treatment of bulbus oculi prolapse in domestic cats. A female calico cat named Mici presented with a chronic left eye injury that had become infected, leading to inflammation and persistent ocular discharge. The cats body weight was 0.7 kg, and its temperature was 38.2C. Surgical treatment was performed using an enucleation technique. The procedure involved an incision along the mid-anterior eyelid, extending to the lower eyelid. Dissection was carried out to expose the bulbus oculi, which was then ligated and excised. The eyelid margins were sutured using simple interrupted sutures. Postoperatively, the cat was administered antibiotics and antihistamines.